(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Radiographic diagnosis of odontogenic cysts and tumors requires proper diagnosis to facilitate successful treatment. Although many types of imaging modalities exist, the relative diagnostic performance of these modalities is not well established. Methods This paper sought to review the literature on the effectiveness of panoramic radiography, CBCT, and CT to detect these jaw lesions. It was a systematic review and meta-analysis according to PRISMA guidelines. After a thorough search in four databases (PubMed, Embase, Scopus, Web of Science) that were published between 2015 and 2024, 8 eligible comparative studies were found. The information on diagnostic accuracy and significant imaging findings was retrieved. ROBINS-E was used to assess risk of bias, and meta-analyses (random-effects with subgroup) were conducted. Results It was shown that CBCT has a major advantage over panoramic radiography in terms of diagnosis, and the studies showed a substantial increase in accuracy (e.g., 70.4% to 85.2%). CBCT has always offered better visualization of such critical features as cortical perforation and root resorption. On the contrary, the efficacy of CBCT and MDCT was similar regarding the bony assessment. Subgroup analysis showed that comparison type (CBCT vs. Panoramic vs. CBCT vs. MDCT) explained more than 76% of the heterogeneity of the results observed. Mixed jaw lesions had strong evidence but inconclusive evidence of individual organizations, such as ameloblastoma. Conclusion CBCT is a better choice over panoramic radiography in the diagnosis of odontogenic lesions since it gives a better 3D detail that increases diagnostic accuracy and surgical planning. It is as efficient as MDCT and with a lesser amount of radiation in most of the bony assessments. Its functions of distinguishing between certain forms of lesions need further research. BJMS, Vol. 25 No. 02 April’26 Page: 423-435